Assessment of Shopping Centres Attractiveness for Young Consumers – Application of Structural Modelling - Szymańska, Anna Irena; Płaziak, Monika (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2020)
The main purpose of the article was to identify the key determinants of young consumers’ behaviour in terms of choosing shopping centres as places for using the commercial and service offer. This identification was based on an analysis of the available literature on the subject and verification of the impact of selected determinants on specific consumer behaviour. The article presented four research hypotheses and a theoretical model, which was then verified using structural modelling (SEM). The developed model was also analysed in terms of the level of reliability and good fit. Based on the statistical analyses it was found that the modified structural equation model had all statistically significant coefficients, which allowed it to be considered relatively satisfying. This enabled the positive verification of three out of four research hypotheses. As a result of the applied structural modelling, statistically significant relationships were observed between the specified groups of factors, such as: personal factors, the specificity of the shopping centre and situational factors, and the visit of the shopping centre by young consumers. What is more, in the respondents’ opinion, the specificity of the shopping centre and situational factors were characterized by a significantly greater impact force on the tested respondents’ behaviour than personal factors. The modelling used data obtained as part of empirical research conducted on a group of 550 respondents.